Transnational cooperation: a network analysis of town twinning in the Baltic Sea region. Issue 3 (3rd July 2018) - Bussmann, Margit; Nickel, Sebastian
ABSTRACT: The patterns of cooperation between regions and urban spaces are no longer influenced, to the same extent, by national borders. Political integrative events changed the extent of transborder urban cooperation in the Baltic borderlands, a region that has undergone extensive changes. A social network analysis of cooperative ties in the form of town twinning indicates that the end of the Cold War strongly changed the network of town twinning in this region, whereas the effect of the various EU enlargement rounds seems to be more nuanced.